Protection of Reputed Trademarks and Keywords: Looking for Ariadne’s Thread Among Flowers, Perfumes and Bags - Elisa Moro (UCL Journal of Law and Jurisprudence, 2015)
Historically, in the majority of judicial systems, the protection of trademarks with reputation differs from the protection of normal trademarks. It is widely recognised that reputed trademarks have an “added value” deserving wider protection. The contribution analyses the evolution of the protection of trademarks with reputation in the European Union legislation and the jurisprudence of the Court of Justice of the European Union (CJEU). The First Directive strengthened the protection of trademarks with reputation both in the field of registration and in the field of infringement. Article 5(2) of the TMD leaves to Member States the possibility to protect well-known trademarks against dilution. Third parties can be prevented by the proprietor of the trademark with reputation from using signs identical or similar to this trademark. The use must take place in the course of trade, the products or services with which it is related should be similar to those for which the trademark is registered and it must take unfair advantage of the distinctiveness of the trademark or be detrimental to it. Considering the internet features, its availability worldwide and the growing number of users, it is evident that is essential for a trademark to expand its reputation and monitor if it is used by third parties that can damage its reputation or take advance of it. The protection of reputed trademarks on the internet is very discussed and problematic. Many actions have been brought for trademark infringement by the use of similar or identical signs ad keywords in search engines. The ECJ tried to order and clarify the application of EU legislation to these particular cases (Vuitton v Google, L'Oreal v Ebay and Interflora v Marks and Spencer). Read more